HARAJUKU STREET OF THE MURAL - Asri Puspitasari; Amin Sulistiyowati; Salim (Canthing, 2021)
Clothing is everything we wear from head to toe, the clothes we wear also reflect our personality and social status, and can convey a message to someone who sees it. The author raised the theme of harajuku street of the mural which was inspired by the street style of Harajuku combined with mural art by street artists. Because it shows that the merging of two different elements is able to create something newer and contemporary.Keywords: Harajuku street of the mural